Body mesurements and heart morphology of water polo players - Vertommen, L.; Clarys, J. P.; Welch, E. W. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
This study was done to describe the mean body build and heart morphology of a group of Belgian water polo players and to study any possible relationship between external morphology and heart size.